2011
DOI: 10.1002/iub.580
|View full text |Cite
|
Sign up to set email alerts
|

TRIM family: Pleiotropy and diversification through homomultimer and heteromultimer formation

Abstract: SummaryThe TRIM family is composed of multidomain ubiquitin E3 ligases characterized by the presence of the N-terminal tripartite motif (RING, B-boxes, and coiled coil). TRIM proteins transfer the ubiquitin moiety to specific substrates but are also involved in ubiquitin-like modifications, in particular SUMOylation and ISGylation. The TRIM family members are involved in a plethora of biological and physiological processes and, when altered, are implicated in many pathological conditions. Growing evidence indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
122
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 66 publications
1
122
0
Order By: Relevance
“…32 Accumulating data indicate that the TRIM family represents one of the largest classes of single-protein, RING-containing, E3 ubiquitin-ligases. 33,34 We and others have demonstrated that Trim17 is a bona fide E3 ubiquitin-ligase. 25,35 In addition, we have shown that the E3 activity of Trim17 is both necessary and sufficient for the initiation of neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…32 Accumulating data indicate that the TRIM family represents one of the largest classes of single-protein, RING-containing, E3 ubiquitin-ligases. 33,34 We and others have demonstrated that Trim17 is a bona fide E3 ubiquitin-ligase. 25,35 In addition, we have shown that the E3 activity of Trim17 is both necessary and sufficient for the initiation of neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tripartite motif (TRIM) E3 ligases constitute one of the largest subfamilies of RING E3s and regulate many cellular processes with a large proportion of TRIM family members being important in the regulation of innate immune responses (Meroni & Diez‐Roux, 2005; Hatakeyama, 2011; Napolitano & Meroni, 2012; Rajsbaum et al , 2014). TRIM ligases share a conserved domain architecture that consists of an N‐terminally located TRIM motif and a C‐terminal region of variable composition that often contains protein interaction domains and may act as a substrate‐recognition module.…”
Section: Introductionmentioning
confidence: 99%
“…"Linker" segments of unknown structure typically separate both the RING and B-box domains (L1) and the coiledcoil and terminal effector domains (L2). The coiled-coil region mediates oligomerization, and both homooligomeric and heterooligomeric TRIMs have been described (7)(8)(9)(10)(11)(12)(13). Furthermore, many TRIM proteins form higher-order assemblies in vitro and form punctate or fibrous structures in cells (14)(15)(16).…”
mentioning
confidence: 99%